2022
DOI: 10.3389/fmed.2022.966620
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of the uterus in the third trimester after high-intensity ultrasound ablation in adenomyosis: A case report

Abstract: Adenomyosis is a benign uterine disease. Due to the higher incidence of adenomyosis and patients' demands for fertility, high-intensity ultrasound ablation has been widely used in gynecological patients with uterine fibroids and adenomyosis. Ultrasound ablation of lesions can help alleviate symptoms in patients without increasing the incidence of obstetric complications in subsequent pregnancies. High-intensity ultrasound ablation is not considered a risk factor for uterine rupture. However, we describe a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Recently, two papers reported 2 cases of uterine rupture in pregnancy after HIFU treatment for adenomyosis due to the adenomyotic lesion was over treated. Fortunately, both patients recovered well and the neonates were healthy 25,26 . In this study, the NPV ratio for adenomyosis in patients who conceived after HIFU was 42.0 +-23.2%.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, two papers reported 2 cases of uterine rupture in pregnancy after HIFU treatment for adenomyosis due to the adenomyotic lesion was over treated. Fortunately, both patients recovered well and the neonates were healthy 25,26 . In this study, the NPV ratio for adenomyosis in patients who conceived after HIFU was 42.0 +-23.2%.…”
Section: Discussionmentioning
confidence: 93%
“…A study found that HIFU treatment for adenomyosis does not increase the risk of uterine rupture [22]. We reviewed the literature and found only two patients who had uterine rupture during delivery after HIFU treatment [23,24]. However, the correlation between HIFU treatment for adenomyosis and uterine rupture cannot be explained.…”
Section: Discussionmentioning
confidence: 98%
“…In this research, we characterized the presence of CTLs, Tc17, Th1, and ThGM cells in patients with focal or diffuse AM before and after focused ultrasound ablation surgery (FUAS). FUAS is a noninvasive procedure that uses high‐intensity ultrasound to generate an instant temperature increase to induce coagulation necrosis of the targeted lesion [24]. We found that these T cell subsets were increased in the blood and AM tissues of patients especially those with diffusive AM.…”
Section: Introductionmentioning
confidence: 87%